Perfil etiológico dos agentes fúngicos em pacientes acometidos por Onicomicoses procedentes dos hospitais universitários de Cuiabá – MT, 2007 - 2011 - Mahfouz, Ana Paula Zanetti Feuser (2012)
The fungal nail are cosmopolitan infections, mainly caused by fungi of the group of dermatophytes, yeasts and non-dermatophytes. This research aims to verify the occurrence of onychomycosis, determining age, sex and anatomical site of patients affected by them, as well as the etiology of these infections. The population in this study consisted of 586 patients with clinically suspected onychomycosis who received medical care and laboratories exams in universities hospitals in Cuiabá (being 398 patients from hospital A and hospital B 188) during the period from January 2007 to December 2011. This was an observational and retrospective study conducted by analyzing data in medical and laboratory records. In relation to the studied population (n=586) was observed positive result in culture for fungi in 294 patients. Of these, 331 were clinical collected specimens, being 77.6% corresponding to the group of yeasts (74.9% belonging to the genus Candida and the genus Trichosporon 2.7%), 12.7% corresponding to dermatophytes (8.8% relative only to T. rubrum) and 9.7% to the group of nondermatophyte molds, being 8.5% related to the isolation of Fusarium spp. The group most affected was that constituted of patients with 46-60 years (35, 1%) and less frequently represented by age group below 15 years, and the nails of the hands is the anatomical site most affected in both sexes. In summary, the yeast in the study population occupied a prominent position in relation to the etiologic profile of onychomycosis, followed by dermatophytes and non-dermatophyte fungi. According to the clinical criteria for onychomycosis, we noticed that only half of the cases had laboratory confirmation (positive culture), despite the good correlation found between mycological examination and culture.